Hyaluronic Acid Intra-Articular Injections in Patients Affected by Moderate to Severe Glenohumeral Osteoarthritis: A Prospective Randomized Study - Di Giacomo, G.; de Gasperis, N. (Joints, 2017)
Purpose The aim of this study was to evaluate the efficacy and safety of intra-articular injection treatment with high molecular weight HA (Hyalubrix, 30 mg/2 mL, molecular weight > 1,500 kDa) in patients affected by moderate to severe glenohumeral osteoarthritis (OA).Methods Seventy-eight patients, affected by shoulder OA grade II–IV were randomized in two groups. Patients included in case group were treated with three intra-articular injections of HA and a specific physiotherapy program, whereas patients included in the control group received the only physical therapy. The follow-up examination was 6 months for both groups. The evaluation of functional status of treated shoulder, range of motion, and pain was performed before treatment and at the final follow-up examination by means of the Constant score. The safety evaluation of the treatment was also performed recording any adverse events.Results Statistical analysis revealed a significant difference (p < 0.05) between the two groups in terms of pain reduction and improvement in the activities of daily living. In particular, case group subjects affected by grade III and IV OA had a significant improvement in the Constant score (18.2 ± 5.4 and 19.2 ± 5.9, respectively).Conclusion This study showed that the combination of intra-articular injection of hyaluronic acid (Hyalubrix, 30 mg/2 mL) with physical therapy program was more effective in comparison with the only physical therapy in reducing pain in patients affected by glenohumeral OA.Level of Evidence Level II, randomized controlled study.
Keywords: hyaluronic acid; injection; glenohumeral; osteoarthritis; shoulder